Family Schools in Enhancing Gender Partnerships and Socio-psychological and Cultural Resilience - Rahmi, Alfi; Januar, Januar; Yusra, Hannilfi; Sabilan, Sapie; Mayang, Mayang; Ramayola, Ramayola (Sawwa: Jurnal Studi Gender, 2025)
Inequality in gender roles is still one of the causes of low psycho-social and sociocultural resilience in families. In response to this issue, the Family School Program is present to build equal gender partnerships and strengthen family resilience. This study used a quantitative approach with descriptive analysis, involving 86 purposively selected Family School participant families. The instrument used was the Family Resilience questionnaire from the Ministry of PPPA. The results showed that 77 families had implemented gender partnership, while 9 had not. A total of 54 families had socio-psychological resilience, and 73 families showed sociocultural resilience. Overall, 19 families were rated as low resilience, 63 as moderate, and only 3 as high. This research shows that most families are at the medium level of resilience. This study looks at the integration of gender and cultural perspectives in the context of family strengthening and contributes to more effective family-school development programs and psycho-social and local value-based interventions.